Ways To Work with Difficult Sounds in The Pronunciation of Younger Students - Olimova Nilufar Qosimjon Qizi (Zien Journals, 2021)
This article is related to study of difficulties face by younger students in learning aur acquiring the phonic knowledge and its pronunciation and way to work with this difficulties.
Keywords: Pronunciation; phonic knowledge; speech